Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.biortech.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvest date on Arundo donax L. (giant reed) composition, ensilage performance, and enzymatic digestibility

Abstract: Composition and ensilage performance of giant reed harvested in August, October, November, and December, were evaluated and compared. Generally, late-harvested giant reed had higher dry matter content, lower nitrogen content, and higher water soluble carbohydrates (WSC) content than early-harvested giant reed. During 90days of ensilage, giant reed harvested in October, November, and December showed dry matter losses of about 1%, while giant reed harvested in August showed a higher dry matter loss of about 8%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Only raw materials with glucose addition had a significant initial WSC content, between 35% and 53% (VS basis). These amounts were significantly higher than the ones found in the literature for feedstocks that were successfully acidified during ensiling [8,[18][19][20][21][22]. Concerning CM16%S condition, no WSC was observed in the initial sample, since starch is not a water-soluble molecule.…”
Section: Feedstock Characterisationmentioning
confidence: 53%
See 1 more Smart Citation
“…Only raw materials with glucose addition had a significant initial WSC content, between 35% and 53% (VS basis). These amounts were significantly higher than the ones found in the literature for feedstocks that were successfully acidified during ensiling [8,[18][19][20][21][22]. Concerning CM16%S condition, no WSC was observed in the initial sample, since starch is not a water-soluble molecule.…”
Section: Feedstock Characterisationmentioning
confidence: 53%
“…Therefore, nitrogen structure was identical for all conditions. Moreover, it is important to notice that ammonia nitrogen content was quite high in feedstocks (15)(16)(17)(18)(19)(20)(21)(22). This might cause substantial ammonia emissions if pH moves toward alkalinity during the storage period [3,12].…”
Section: Feedstock Characterisationmentioning
confidence: 99%
“…However, as Zheng, Zhao, Xu, and Li () pointed out, ensiling can have a positive effect on methane yield and can be seen as a pretreatment for miscanthus biomass. Also Liu et al () found a higher digestibility for ensiled compared to non‐ensiled biomass (giant reed). This explains the higher velocity and specific methane yields of ensiled miscanthus compared to non‐ensiled miscanthus.…”
Section: Discussionmentioning
confidence: 96%
“…The quality of silage can be measured by various parameters, for example, silage acids and pH value. The two acids, lactic acid and butyric acid, are often used to classify silage quality, as a high level of lactic and low level of butyric acid indicate silage of good quality (Galler, ; Liu, Ge, Liu, & Li, ). A number of studies recommend a pH value within the range of 3.7–4.5 to achieve a sufficient silage quality (Galler, ; Liu et al, ; Teixeira Franco, Buffière, & Bayard, ; Vervaeren, Hostyn, Ghekiere, & Willems, ).…”
Section: Discussionmentioning
confidence: 99%
“…The glucose content was higher in the leaves than in the roots, and while there were no differences in the content by collection time in the roots, the glucose content increased five times in the leaves from 0.20% in October to 1.04% in December, a significant difference. Liu S et al (25) measured the free sugar content of Arundo donax L. by harvest time and reported that the Each value is expressed as mean±SD, n=3.…”
Section: Free Sugarsmentioning
confidence: 99%